Implementation of supporting, practice-based learning activities in short geology and soil science modules in landscape architecture and natural resource management curricula - Callesen, Ingeborg (Improving University Science Teaching and Learning, 2023)
This study tested the use of practical exercises on campus made possible by recorded lectures as a means to create variation in basic soil science courses. Curriculum changes from one discipline to multi-disciplinary courses including soil science, geology, geomorphology, chemistry, botany, ecology, plant physiology etc. has increased the risk of subject matter overload in relation to time and textbook materials over the last decade. Soil science teachers and students expressed the need for re-introducing practical hands-on teaching and learning activities in order to achieve competencies in soil, site and landscape evaluation e.g. with respect to suitability for tree growth. Teachers on multi-disciplinary courses are encouraged to work as teams to ensure balanced teaching and learning activities and avoid overload of subject matter from competing disciplines.